ANALISIS PERUBAHAN KEBIJAKAN QATAR MENANGANI PEKERJA MIGRAN TAHUN 2010-2020 - Intan Zaleha Permata Sari; Anita Afriani Sinulingga; Inda Mustika Permata (Jurusan Ilmu Hubungan Internasional, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Sriwijaya, 2021)
Qatar is a popular destination for migrant workers and ever become the world’s highest ratio of migrants to citizens. For decades, Qatar has adopted the Kafala System. Recently, Qatar received international spotlight due to human rights violation during preparations for the 2022 FIFA World Cup. In 2015, Qatar took step to change Kafala System but half of population still wants to maintain the system. The Government finally issued a policy in 2020 as the end of Kafala System’s reform. This research aims to explain the factors that have influenced policy changes for migrant workers in Qatar from 2010 to 2020. This research is analyzed with foreign policy change as conceptual framework proposed by Spyros Blavoukos and Dimitris Bourantonis. Research method used in this research is qualitative method and the type of research is descriptive analysis by using secondary data. According to the concept, this research found that Qatar has made changes to migrant worker’s policies due to conditions such as the Gulf Crisis, participation in the international system, political-institutional setting and policy making process, and change of leadership in 2013.